Chapter 22 Towards a Better Understanding of Energy Poverty - Dunphy, Niall P. (Taylor & Francis, 2024)
Living with Energy Poverty: Perspectives from the Global North and South expands our collective understanding of energy poverty and deepens our recognition of the phenomenon by engaging with the lived experiences of energy-poor households across different contexts. Understanding the lived experience of energy poverty is an essential component in the design of any effort to alleviate what is fundamentally a deep-rooted, multi-faceted, wickedly complex problem. This requires a nuanced understanding of the causal factors and the research methods that can respond to the flexible spatial and temporal nature of the condition, as well as its wellbeing and justice implications. Drawing together the expertise and connectedness of authors from the Global South and North, this book presents novel approaches to understanding the often hidden forms of domestic energy deprivation. Case studies from 20 countries provide critical perspectives on this phenomenon while analysing the policy practices, government strategy, and sustainability implications of divergent manifestations. The book takes a multidimensional perspective, challenging the bias towards energy production and service provision, which often do not align with the aspirations and realities of energy households across global contexts, thus facilitating a useful dialogue on the nature of energy poverty. The book is a timely source for policymakers, practitioners, and scholars seeking fresh, diverse insights into the everyday reality of energy poverty and wanting to better understand the challenges a people-centred, just energy transition can present.